Differentiation and long-term survival of C2C12 myoblast grafts in heart. - Koh, G Y (1993)
We have assessed the ability of skeletal myoblasts to form long-term, differentiated grafts in ventricular myocardium. C2C12 myoblasts were grafted directly into the heart of syngeneic mice. Viable grafts were observed as long as 3 mo after implantation. Immunohistological analyses revealed the presence of differentiated myotubes that stably expressed the skeletal myosin heavy chain isoform. Thymidine uptake studies indicated that virtually all of the grafted skeletal myocytes were withdrawn from the cell cycle by 14 d after grafting. Graft myocytes exhibited ultrastructural characteristics typical of differentiated myotubes. Graft formation and the associated myocardial remodeling did not induce overt cardiac arrhythmia. This study indicates that the myocardium can serve as a stable platform for skeletal myoblast grafts. The long-term survival, differentiated phenotype, and absence of sustained proliferative activity observed in myoblast grafts raise the possibility that similar grafting approaches may be used to replace diseased myocardium. Furthermore, the genetic tractability of myoblasts could provide a useful means for the local delivery of recombinant molecules to the heart.